A method for preparing refined cadmium by deep replacement of double-size zinc powder by ultrasonic enhancement

Through the ultrasonic enhanced double-particle zinc powder replacement method, the problems of high zinc powder consumption in copper-cadmium slag and high zinc content in sponge cadmium were solved, and the preparation of high-grade sponge cadmium and efficient cadmium recovery were achieved.

CN120425165BActive Publication Date: 2025-09-12KUNMING UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510927532.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-07
Publication Date
2025-09-12
Estimated Expiration
2045-07-07

AI Technical Summary

Technical Problem

In the prior art, when zinc powder is replaced in copper-cadmium slag, the surface energy of small-sized zinc powder is large, and the metallic cadmium generated on the surface is difficult to peel off, resulting in high consumption of replaced zinc powder and high zinc content in sponge cadmium.

Method used

An ultrasonically enhanced dual-particle zinc powder deep replacement method is adopted, in which small-particle zinc powder is used to quickly replace Cd2+. Ultrasound is used to guide the collision and shattering of large-particle zinc powder and small particles, and the irregular movement is guided by ultrasonic energy to prevent the zinc powder from sticking, thereby achieving deep replacement of cadmium.

Benefits of technology

The prepared sponge cadmium has a high grade of 97.11%, and more than 99.1% refined cadmium can be obtained after one smelting, effectively reducing the consumption of zinc powder and improving the cadmium recovery efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120425165B_ABST
    Figure CN120425165B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing refined cadmium by deep replacement of double-particle zinc powder enhanced by ultrasonic technology, belonging to the technical field of cadmium recovery in copper-cadmium slag. The present invention includes five steps: slurrying, neutral leaching, ultrasonic-enhanced replacement, refining and casting, and secondary replacement. Slurrying washes out the encapsulated zinc sulfate, neutral leaching controls the endpoint pH to separate copper and cadmium, and ultrasonic replacement achieves the separation of zinc powder and cadmium through surface action (small particle size) and collision action (large particle size). 2+ During the refining and casting process, alkali and zinc are added to form a slag; during the secondary replacement process, screened large-particle zinc powder is added to reduce the cadmium content of the leachate. The present invention incorporates ultrasound during the dual-particle zinc powder replacement process, effectively guiding the irregular movement and scouring of large and small particles, achieving deep cadmium replacement and reducing zinc powder usage. The sponge cadmium grade of the present invention can reach 97.11%, and after a single smelting step, refined cadmium with a grade exceeding 99.1% can be obtained, reducing overall zinc powder consumption to 8.62 kg per 100 kg of copper-cadmium slag.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing refined cadmium by deep replacement of double-granularity zinc powder enhanced by ultrasonic, and belongs to the technical field of cadmium recovery in copper-cadmium slag. Background Art

[0002] Cadmium is present in very small amounts in the earth's crust, accounting for only about 0.005‰. There are no independent deposits. Currently, about 95% of cadmium is recovered from copper-cadmium slag produced by zinc leaching. The current process for recovering cadmium from copper-cadmium slag is mainly "acid leaching-zinc powder replacement-sponge cadmium pressing-cadmium refining". During the replacement, the Cd in the leachate is 2+ The zinc atoms exchange electrons with the zinc powder particles, and the zinc atoms lose electrons to generate Zn 2+ Entering the solution, Gd 2+ The electrons are generated to form metal cadmium which grows at the particle interface. As the replacement reaction proceeds, the surface of the zinc powder is completely covered with the generated layer of metal cadmium. The Cd in the leachate 2+ Unable to come into contact with zinc powder, the replacement reaction cannot proceed, resulting in cadmium-coated zinc, resulting in low-grade sponge cadmium. Domestic scholars have studied zinc particle vibration purification, ultrasonic enhanced zinc powder replacement, and microcurrent regulation. Essentially, these methods cause the generated sponge cadmium to fall from the surface of the zinc particles, continuously exposing new zinc surfaces. However, the surface energy of zinc powder is large, and when the replacement reaches a certain level, the van der Waals force between the metal cadmium and the zinc powder increases to a significant degree, preventing the metal cadmium from peeling off. This results in high consumption of replacement zinc powder and a high zinc content in the sponge cadmium. Summary of the Invention

[0003] In view of the current problems in the replacement of cadmium zinc powder with copper-cadmium slag, such as the large surface energy of small-particle zinc powder, the difficulty in stripping the metallic cadmium generated on the surface, resulting in high consumption of replacement zinc powder and high zinc content in sponge cadmium, the present invention proposes a method for preparing refined cadmium by deep replacement of double-particle zinc powder with ultrasonic enhancement. 2+ The displacement power is large, and the displacement reaction can occur quickly. The surface energy of large-sized zinc powder is small, and it can react with Cd 2+ The displacement power is small, it is not easy to wrap, and the inertia is large. During the collision with small zinc particles during the displacement, the surface wrapping of the small particles can be broken, revealing a fresh interface. During the ultrasonic enhanced displacement reaction, there are double-sized zinc powders in the system, and the small zinc particles and Cd are separated by surface action and collision. 2+ The inner layer is replaced by a single-stage replacement process, producing a high-grade cadmium sponge. Ultrasound, introduced during the first stage of replacement, effectively guides the irregular movement and scouring of large and small zinc particles, preventing small-particle zinc powder from adhering to each other. During the second stage of replacement, only large-particle zinc powder is added to reduce the cadmium content in the leachate and prevent cadmium from re-dissolving. The resulting zinc-cadmium slag is then returned to the first stage of replacement for further replacement. The cadmium sponge produced by this method has a grade of up to 97.11%, and a single smelting step can yield refined cadmium with a grade exceeding 99.1%.

[0004] A method for preparing refined cadmium by deep replacement of double-size zinc powder by ultrasonic enhancement, comprising the following steps:

[0005] (1) adding the copper-cadmium slag into water for slurry treatment, performing solid-liquid separation to obtain filtrate I and filter residue I, and returning the filtrate I to the zinc production process;

[0006] (2) adding the filter residue I to the waste electrolyte, mixing them evenly and performing neutral leaching. During the leaching process, zinc oxide fume is added to adjust the pH value of the leaching system to 1.5-4 to prevent copper leaching. Solid-liquid separation is performed to obtain copper-containing slag and filtrate II;

[0007] (3) adding small-particle zinc powder and large-particle zinc powder to filtrate II to carry out ultrasonic enhanced replacement reaction, screening out the large-particle zinc powder, and performing solid-liquid separation to obtain sponge cadmium and filtrate III;

[0008] (4) Pressing the sponge cadmium into a mass, adding alkali to smelt it, introducing air to stir and remove zinc, and casting to obtain a refined cadmium ingot;

[0009] (5) The large-particle zinc powder sieved out in step (3) is added to the filtrate III to carry out a secondary replacement reaction, and the solid-liquid separation is performed to obtain the filtrate IV and the zinc-cadmium slag. The filtrate IV is returned to step (1) for the copper-cadmium slag slurry treatment, and the zinc-cadmium slag is returned to step (3) for the ultrasonic enhanced replacement reaction.

[0010] Preferably, in terms of mass percentage, the Zn content in the copper-cadmium slag in step (1) is 15%-40%, the Cu content is 4.00%-20%, the Cd content is 12.00%-40%, the S content is 2.21%-13.73%, the O content is 4.40%-27.39%, and the content of other elements is 2.88%-18.39%; wherein, in the zinc phase, the metallic zinc phase accounts for 30%-70%, and the zinc sulfate phase accounts for 30%-70%.

[0011] Preferably, the slurrying temperature in step (1) is 50-80°C, the slurrying time is 20-60 min, the liquid-solid ratio (mL:g) of the slurrying treatment is 1:2-2:1, and the zinc content in the filtrate I is 90-140 g / L; in terms of mass percentage, the zinc content in the filter residue is 11.81%-38.85%, the mass of Cu is 12.95%-25.93%, the mass of Cd is 38.43%-45.00%, and the mass of other elements is 9.33%-20.69%.

[0012] Preferably, the zinc content in the waste electrolyte in step (2) is 30-80 g / L, and the acidity is 120-170 g / L; in terms of mass percentage, the zinc content in the zinc oxide fume is 40-60%, and the lead content is 8-15%; in the zinc phase of the zinc oxide fume, ZnO accounts for 80%-92%, and ZnS accounts for 8%-20%, and in the Pb phase, PbO accounts for 40%-60%, and PbSO4 accounts for 40%-60%; the liquid-solid ratio of the waste electrolyte to the filter residue I, mL:g, is 3.5:1-8:1; the neutral leaching temperature is 70-90°C, and the leaching time is 1-3 h.

[0013] Preferably, in terms of mass percentage, the copper content in the copper-containing slag of step (2) is 80.05-96.45%, the zinc content is 0.75-3.84%, the cadmium content is 0.60-1.22%, and the Pb content is 0.83-6.43%; the zinc content in the filtrate II is 37.38-55.50 g / L, the Cu content is 0.08-0.32 g / L, and the Cd content is 48.33-127.46 g / L.

[0014] Preferably, in step (3), the particle size of the small-particle zinc powder is 60-200 mesh, the particle size of the large-particle zinc powder is 0.4-1 cm, the amount of the small-particle zinc powder added is 8.41%-23.46% of the mass of the copper-cadmium slag, and the amount of the large-particle zinc powder added is 0.21%-0.72% of the mass of the copper-cadmium slag; the total zinc content in the zinc powder is 98%-99.5%, the metallic zinc content is 95%-98%, and the impurity content is 0.50%-2%; the ultrasound is transient cavitation ultrasound, and the ultrasound amplitude is 1.8-3 bar r; the temperature of the ultrasonic-enhanced replacement reaction was 45-55℃, the time was 30-75min, and the pH endpoint was 4-4.8; in terms of mass percentage, the cadmium content in the sponge cadmium was 96.81%-97.11%, the zinc content was 2.88%-2.96%, and the Cu content was 0.082%-0.17%; the cadmium content in the filtrate III was 0.48-1.28 g / L, the zinc content was 83.78-111.26 g / L, and the copper content was 0.04-0.16 g / L.

[0015] Preferably, the alkali in step (4) is sodium hydroxide, calcium hydroxide or potassium hydroxide, the smelting temperature is 420-550° C., the smelting time is 1.5-4 h, and the amount of alkali added is 10%-35% of the mass of the sponge cadmium; the cadmium content in the refined cadmium ingot is 99.1-99.9 wt.%, and the zinc content is 0.0008-0.004 wt.%.

[0016] Preferably, the particle size of the large-particle zinc powder in step (5) is 0.4-1 cm, the replacement temperature is 55-65° C., the pH end point is 4.8-5.5, and the time is 75-120 min; the cadmium content in the filtrate IV is 0.02-0.64 g / L, and the zinc content is 83.78-112.39 g / L; in terms of mass percentage, the Cd content in the zinc-cadmium slag is 18.90%-21.14%, and the zinc content is 75.18%-76.37%.

[0017] The curves of cavitation bubble radius changing with time under different ultrasonic intensities are shown in Figure 2 ,from Figure 2 It can be seen that when the ultrasonic sound pressure is between 0.8 and 1.6 bar, the radius of the cavitation bubble changes little, and the limit size of the cavitation bubble radius does not exceed 2 times the initial radius. Cavitation is mainly steady-state cavitation, and the bubbles can expand and contract stably, and the cavitation effect is weak. When the sound pressure amplitude varies between 1.8 and 2.0 bar, as the sound pressure amplitude increases, the amplitude of the change in the cavitation bubble radius increases, and the limit size of the cavitation bubble increases from the initial 13 times to 50 times, at which time the cavitation bubble collapses. When the sound pressure amplitude reaches 4.0 bar, the time required for the bubble to collapse is close to one ultrasonic cycle. At this time, if the sound pressure continues to increase, it will cause the tiny bubbles in the solution to be unable to participate in the next complete cavitation cycle, limiting subsequent cavitation behavior. This proves that the ultrasonic cavitation effect does not continue to increase with the increase of sound pressure. When it exceeds a certain threshold, the effect of ultrasonic cavitation is weakened. Therefore, when this application adopts ultrasonic enhanced displacement, the ultrasonic amplitude is 1.8 to 3 bar.

[0018] The beneficial effects of the present invention are:

[0019] (1) The present invention first uses slurry water to wash out zinc sulfate in the copper-cadmium slag. The slurry has few impurities and high zinc content, and can be directly returned to the zinc smelting system;

[0020] (2) The present invention utilizes smoke dust to adjust the pH during acid leaching of copper-cadmium slag to prevent copper leaching, thereby achieving efficient separation of copper and cadmium, with the copper content in the copper-containing slag reaching 96.45%;

[0021] (3) When the cadmium-containing leaching solution of the present invention is subjected to ultrasonic enhanced replacement enrichment, double-sized zinc powder exists in the system, and the small-sized zinc powder replaces the Cd 2+ The high surface energy allows for rapid replacement. During collisions between large and small zinc powder particles, the surface coating of the small particles can be shattered, enabling secondary replacement of the coated small zinc powder. Ultrasound, introduced during this replacement process, effectively guides the irregular movement and scouring of large and small particles, preventing adhesion of small zinc powder particles. This allows for deep replacement of cadmium and significantly reduces the amount of zinc coating. The cadmium sponge prepared by this method has a grade of up to 97.11%, and refined cadmium with a grade of over 99.1% can be obtained through a single smelting step. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a process flow chart of the present invention;

[0023] Figure 2 The curves of cavitation bubble radius changing with time under different ultrasonic intensities, (a) is the ultrasonic intensity of 0.8~1.6 bar, (b) is the ultrasonic intensity of 1.8~2.0 bar, and (c) is the ultrasonic intensity of 4.0~10.0 bar. DETAILED DESCRIPTION

[0024] The present invention will be further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the contents described above.

[0025] Example 1: The main components of the copper-cadmium slag in this example are shown in Table 1.1, and the zinc phase in the copper-cadmium slag is shown in Table 1.2;

[0026] Table 1.1 Main components of copper-cadmium slag (mass percentage)

[0027] ;

[0028] Table 1.2 Zinc phase in copper-cadmium slag

[0029] ;

[0030] A method for preparing refined cadmium by deep replacement of double-size zinc powder with ultrasonic enhancement (see Figure 1 ), the specific steps are as follows:

[0031] (1) Slurrying: copper-cadmium slag was added to water and slurried at 50°C for 20 min. The solid-liquid separation was performed to obtain filtrate I and filter residue I. The filtrate I was returned to the zinc production process. The liquid-solid ratio of the slurrying treatment was 2:1 in mL:g. The zinc content in the filtrate I was 140 g / L, the zinc content in the filter residue was 38.85%, the mass content of Cu was 12.95%, the mass of Cd was 38.86%, and the mass of other elements was 9.33%.

[0032] (2) Neutral leaching: Add filter residue I to the waste electrolyte, mix evenly, and perform neutral leaching at 70°C for 1 hour. During the leaching process, zinc oxide dust is added to adjust the pH value of the leaching system to 1.5 to prevent copper leaching. Solid-liquid separation is performed to obtain copper-containing slag and filtrate II. The zinc content in the waste electrolyte is 30 g / L and the acidity is 120 g / L. In terms of mass percentage, the zinc content in the zinc oxide dust is 45% and the lead content is 15%. ZnO accounts for 80% of the zinc phase in the zinc oxide dust. , ZnS accounted for 20%, PbO accounted for 40% and PbSO4 accounted for 60% in the Pb phase; the liquid-solid ratio of the spent electrolyte to the filter residue I was 8:1 in mL:g; the zinc content in the filtrate II was 50.41 g / L, the Cu content was 0.08 g / L, and the Cd content was 48.33 g / L; in terms of mass percentage, the copper content in the copper-containing slag was 80.90%, the zinc content was 3.83%, the cadmium content was 1.22%, and the Pb content was 4.34%. The copper-containing slag can be sold directly;

[0033] (3) Ultrasonic enhanced replacement: small-particle zinc powder (60 mesh) and large-particle zinc powder (particle size 0.4 cm) were added to filtrate II, and ultrasonic enhanced replacement reaction was carried out at a temperature of 45 ° C for 30 min until the end pH value was 4 (ultrasound was transient cavitation ultrasound, and the ultrasonic amplitude was 1.8 bar). The large-particle zinc powder was sieved out, and the solid-liquid separation was performed to obtain sponge cadmium and filtrate III; the amount of small-particle zinc powder added was 8.41% of the mass of the copper-cadmium slag, and the amount of large-particle zinc powder added was 0.21% of the mass of the copper-cadmium slag. The total zinc content in the zinc powder was 98%, the metallic zinc content was 95%, and the impurity content was 2%; in terms of mass percentage, the cadmium content in the sponge cadmium was 96.81%, the zinc content was 2.96%, and the Cu content was 0.082%; the cadmium content in the filtrate III was 0.48 g / L, the zinc content was 83.78 g / L, and the copper content was 0.04 g / L;

[0034] (4) Refining and casting: The sponge cadmium is pressed into a mass, alkali (sodium hydroxide) is added, and the smelting is carried out at a temperature of 420°C for 1.5 hours, and air is introduced for stirring to remove zinc, and then a refined cadmium ingot is cast; the amount of alkali added is 10% of the mass of the sponge cadmium; the cadmium content of the refined cadmium ingot is 99.1wt.%, and the zinc content is 0.004wt.%;

[0035] (5) Secondary replacement: the large-particle zinc powder sieved out in step (3) is added to the filtrate III, and a secondary replacement reaction is carried out at a temperature of 55°C for 75 minutes until the end pH value is 4.8, and the solid-liquid separation is performed to obtain a filtrate IV and a zinc-cadmium slag. The filtrate IV is returned to step (1) for slurry treatment of the copper-cadmium slag, and the zinc-cadmium slag is returned to step (3) for ultrasonic enhanced replacement reaction; the cadmium content in the filtrate IV is 0.02 g / L, and the zinc content is 83.78 g / L; in terms of mass percentage, the Cd content in the zinc-cadmium slag is 21.14%, and the zinc content is 75.56%;

[0036] The grade of the refined cadmium ingot prepared in this embodiment is 99.1%, the direct recovery rate of cadmium reaches 98.5%, and the overall consumption of zinc powder is 8.62 kg / 100 kg copper-cadmium slag.

[0037] Example 2: The main components of the copper-cadmium slag in this example are shown in Table 2.1, and the zinc phase in the copper-cadmium slag is shown in Table 2.2;

[0038] Table 2.1 Main components of copper-cadmium slag (mass percentage)

[0039] ;

[0040] Table 2.2 Zinc phase in copper-cadmium slag

[0041] ;

[0042] A method for preparing refined cadmium by deep replacement of double-size zinc powder with ultrasonic enhancement (see Figure 1 ), the specific steps are as follows:

[0043] (1) Slurrying: copper-cadmium slag was added to water and slurried at 65°C for 40 min. Solid-liquid separation was performed to obtain filtrate I and filter residue I. Filtrate I was returned to the zinc production process. The liquid-solid ratio of the slurrying treatment was 1:1 in mL:g. The zinc content in filtrate I was 131.55 g / L, the zinc content in the filter residue was 19.48%, the mass content of Cu was 25.93%, the mass of Cd was 38.43%, and the mass of other elements was 16.16%.

[0044] (2) Neutral leaching: Add the filter residue I to the waste electrolyte, mix evenly and perform neutral leaching at 80℃ for 2h. During the leaching process, zinc oxide dust is added to adjust the pH value of the leaching system to 2.5 to prevent copper leaching. Solid-liquid separation is performed to obtain copper-containing slag and filtrate II. The zinc content in the waste electrolyte is 46.66g / L and the acidity is 153.12g / L. In terms of mass percentage, the zinc content in the zinc oxide dust is 55% and the lead content is 12%. The zinc phase of the zinc oxide dust contains ZnO, which accounts for 10.1% of the total lead content. 88%, ZnS accounts for 12%, PbO accounts for 50%, and PbSO4 accounts for 50% of the Pb phase; the liquid-to-solid ratio of the spent electrolyte to the filter residue I is 5:1 in mL:g; the zinc content of the filtrate II is 55.50g / L, the Cu content is 0.26g / L, and the Cd content is 76.47g / L; in terms of mass percentage, the copper content of the copper-containing slag is 80.05%, the zinc content is 3.84%, the cadmium content is 0.60%, and the Pb content is 6.43%. The copper-containing slag can be sold directly;

[0045] (3) Ultrasonic enhanced replacement: small-particle zinc powder (100 mesh) and large-particle zinc powder (particle size 0.8 cm) were added to filtrate II, and ultrasonic enhanced replacement reaction was carried out at a temperature of 50 ° C for 60 min until the end pH value was 4.5 (ultrasound was transient cavitation ultrasound, and the ultrasonic amplitude was 2.2 bar). The large-particle zinc powder was sieved out, and the solid-liquid separation was performed to obtain sponge cadmium and filtrate III; the amount of small-particle zinc powder added was 15.60% of the mass of the copper-cadmium slag, and the amount of large-particle zinc powder added was 0.51% of the mass of the copper-cadmium slag. The total zinc content in the zinc powder was 99.2%, the metallic zinc content was 96.5%, and the impurity content was 0.8%; in terms of mass percentage, the cadmium content in the sponge cadmium was 97.05%, the zinc content was 2.92%, and the Cu content was 0.17%. The cadmium content in filtrate III was 0.76 g / L, the zinc content was 100.77 g / L, and the copper content was 0.13 g / L;

[0046] (4) Refining and casting: The sponge cadmium is pressed into a mass, alkali (calcium hydroxide) is added, and the smelting is carried out at a temperature of 475°C for 2.5 hours, and air is introduced for stirring to remove zinc, and then a refined cadmium ingot is cast; the amount of alkali added is 20% of the mass of the sponge cadmium; the cadmium content of the refined cadmium ingot is 99.5wt.%, and the zinc content is 0.002wt.%;

[0047] (5) Secondary replacement: the large-particle zinc powder sieved out in step (3) is added to the filtrate III, and a secondary replacement reaction is carried out at a temperature of 60°C for 100 minutes until the end pH value is 5.2, and the solid-liquid separation is performed to obtain a filtrate IV and a zinc-cadmium slag. The filtrate IV is returned to step (1) for slurry treatment of the copper-cadmium slag, and the zinc-cadmium slag is returned to step (3) for ultrasonic enhanced replacement reaction; the cadmium content in the filtrate IV is 0.38 g / L, and the zinc content is 101.33 g / L; in terms of mass percentage, the Cd content in the zinc-cadmium slag is 19.31%, and the zinc content is 75.90%;

[0048] The grade of the refined cadmium ingot prepared in this embodiment is 99.5%, the direct recovery rate of cadmium reaches 99.0%, and the overall consumption of zinc powder is 16.11 kg / 100 kg copper-cadmium slag.

[0049] Example 3: The main components of the copper-cadmium slag in this example are shown in Table 3.1, and the zinc phase in the copper-cadmium slag is shown in Table 3.2;

[0050] Table 3.1 Main components of copper-cadmium slag (mass percentage)

[0051] ;

[0052] Table 3.2 Zinc phase in copper-cadmium slag

[0053] ;

[0054] A method for preparing refined cadmium by deep replacement of double-size zinc powder with ultrasonic enhancement (see Figure 1 ), the specific steps are as follows:

[0055] (1) Slurrying: copper-cadmium slag was added to water and slurried at 80°C for 60 min. The solid-liquid separation was performed to obtain filtrate I and filter residue I. The filtrate I was returned to the zinc production process. The liquid-solid ratio of the slurrying treatment was 1:2 in mL:g. The zinc content in the filtrate I was 131.55 g / L, the zinc content in the filter residue was 90 g / L, the zinc content in the filter residue was 11.81%, the mass of Cu was 22.50%, the mass of Cd was 45.00%, and the mass of other elements was 20.69%.

[0056] (2) Neutral leaching: Add the filter residue I to the waste electrolyte, mix evenly and perform neutral leaching at 90℃ for 3h. During the leaching process, zinc oxide dust is added to adjust the pH value of the leaching system to 4 to prevent copper leaching. Solid-liquid separation is performed to obtain copper-containing slag and filtrate II. The zinc content in the waste electrolyte is 80g / L and the acidity is 170g / L. In terms of mass percentage, the zinc content in the zinc oxide dust is 60% and the lead content is 8%. In the zinc phase of the zinc oxide dust, ZnO accounts for 92% and Zn S accounts for 8%, PbO accounts for 60% and PbSO4 accounts for 40% of the Pb phase; the liquid-to-solid ratio of the spent electrolyte to the filter residue I is 3.5:1 in mL:g; the zinc content of filtrate II is 37.38 g / L, the Cu content is 0.32 g / L, and the Cd content is 127.46 g / L; in terms of mass percentage, the copper content of the copper-containing slag is 96.45%, the zinc content is 0.75%, the cadmium content is 0.97%, and the Pb content is 0.83%. The copper-containing slag can be sold directly;

[0057] (3) Ultrasonic enhanced replacement: small-particle zinc powder (200 mesh) and large-particle zinc powder (particle size 1 cm) were added to the filtrate II, and the ultrasonic enhanced replacement reaction was carried out at a temperature of 55 ° C for 75 minutes until the end pH value was 4.8 (the ultrasound was transient cavitation ultrasound, and the ultrasound amplitude was 3.0 bar). The large-particle zinc powder was sieved out, and the solid-liquid separation was performed to obtain sponge cadmium and filtrate III; the amount of small-particle zinc powder added was 23.46% of the mass of the copper-cadmium slag, and the amount of large-particle zinc powder added was 0.72% of the mass of the copper-cadmium slag. The total zinc content in the zinc powder was 99.5%, the metallic zinc content was 98%, and the impurity content was 0.5%; in terms of mass percentage, the cadmium content in the sponge cadmium was 97.11%, the zinc content was 2.88%, and the Cu content was 0.12%. The cadmium content in the filtrate III was 1.28 g / L, the zinc content was 111.26 g / L, and the copper content was 0.16 g / L.

[0058] (4) Refining and casting: The sponge cadmium is pressed into a mass, alkali (calcium hydroxide) is added, and the smelting is carried out at a temperature of 550°C for 4 hours, and air is introduced to stir to remove zinc, and then a refined cadmium ingot is cast; the amount of alkali added is 35% of the mass of the sponge cadmium; the cadmium content of the refined cadmium ingot is 99.9wt.%, and the zinc content is 0.0008wt.%;

[0059] (5) Secondary replacement: the large-particle zinc powder sieved out in step (3) is added to the filtrate III, and a secondary replacement reaction is carried out at a temperature of 65°C for 120 minutes until the end pH value is 5.5, and the solid-liquid separation is performed to obtain a filtrate IV and a zinc-cadmium slag. The filtrate IV is returned to step (1) for slurry treatment of the copper-cadmium slag, and the zinc-cadmium slag is returned to step (3) for ultrasonic enhanced replacement reaction; the cadmium content in the filtrate IV is 0.64 g / L, and the zinc content is 112.39 g / L; in terms of mass percentage, the Cd content in the zinc-cadmium slag is 20.71%, and the zinc content is 75.18%;

[0060] The grade of the refined cadmium ingot prepared in this embodiment is 99.9%, the direct recovery rate of cadmium reaches 99.5%, and the overall consumption of zinc powder is 24.18 kg / 100 kg copper-cadmium slag.

[0061] The above describes the specific embodiments of the present invention in detail, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in this field without departing from the scope of the present invention.

Claims

1. A method for preparing refined cadmium by deep replacement of double-size zinc powder by ultrasonic enhancement, characterized in that: The specific steps are as follows: (1) adding the copper-cadmium slag into water for slurry treatment, performing solid-liquid separation to obtain filtrate I and filter residue I, and returning the filtrate I to the zinc production process; (2) adding the filter residue I to the waste electrolyte, mixing them evenly and performing neutral leaching. During the leaching process, zinc oxide fume is added to adjust the pH value of the leaching system to 1.5-4 to prevent copper leaching. Solid-liquid separation is performed to obtain copper-containing slag and filtrate II; (3) adding small-particle zinc powder and large-particle zinc powder to filtrate II to carry out ultrasonic enhanced replacement reaction, screening out large-particle zinc powder, and performing solid-liquid separation to obtain sponge cadmium and filtrate III; the particle size of the small-particle zinc powder is 60-200 mesh, the particle size of the large-particle zinc powder is 0.4-1 cm, the amount of small-particle zinc powder added is 8.41%-23.46% of the mass of the copper-cadmium slag, and the amount of large-particle zinc powder added is 0.21%-0.72% of the mass of the copper-cadmium slag; the ultrasound is transient cavitation ultrasound, and the ultrasound amplitude is 1.8-3 bar; (4) Pressing the sponge cadmium into a mass, adding alkali to smelt it, introducing air to stir and remove zinc, and casting to obtain a refined cadmium ingot; (5) The large-particle zinc powder sieved out in step (3) is added to the filtrate III to carry out a secondary replacement reaction, and the solid-liquid separation is performed to obtain the filtrate IV and the zinc-cadmium slag. The filtrate IV is returned to step (1) for the copper-cadmium slag slurry treatment, and the zinc-cadmium slag is returned to step (3) for the ultrasonic enhanced replacement reaction.

2. The method for preparing refined cadmium by deep replacement of double-size zinc powder by ultrasonic enhancement according to claim 1, characterized in that: In terms of mass percentage, the copper-cadmium slag in step (1) has a Zn content of 15% to 40%, a Cu content of 4.00% to 20%, a Cd content of 12.00% to 40%, a S content of 2.21% to 13.73%, an O content of 4.40% to 27.39%, and a content of other elements of 2.88% to 18.39%. Among them, the metallic zinc phase accounts for 30% to 70% of the zinc phase, and the zinc sulfate phase accounts for 30% to 70%.

3. The method for preparing refined cadmium by deep replacement of double-size zinc powder by ultrasonic enhancement according to claim 1 or 2, characterized in that: The slurrying temperature in step (1) is 50-80° C., the slurrying time is 20-60 min, the liquid-to-solid ratio (mL:g) of the slurrying treatment is 1:2-2:1, and the zinc content in the filtrate I is 90-140 g / L. In terms of mass percentage, the zinc content in the filter residue is 11.81%-38.85%, the Cu mass is 12.95%-25.93%, the Cd mass is 38.43%-45.00%, and the mass of other elements is 9.33%-20.69%.

4. The method for preparing refined cadmium by deep replacement of double-size zinc powder by ultrasonic enhancement according to claim 1, characterized in that: In step (2), the zinc content in the waste electrolyte is 30-80 g / L, and the acidity is 120-170 g / L; in terms of mass percentage, the zinc content in the zinc oxide fume is 40-60%, and the lead content is 8-15%; in the zinc phase of the zinc oxide fume, ZnO accounts for 80%-92%, and ZnS accounts for 8%-20%, and in the Pb phase, PbO accounts for 40%-60%, and PbSO4 accounts for 40%-60%; the liquid-solid ratio of the waste electrolyte to the filter residue I is mL:g 3.5:1-8:1; the temperature of the neutral leaching is 70-90°C, and the leaching time is 1-3 h.

5. The method for preparing refined cadmium by deep replacement of double-size zinc powder by ultrasonic enhancement according to claim 1 or 4, characterized in that: In terms of mass percentage, the copper content in the copper-containing slag of step (2) is 80.05-96.45%, the zinc content is 0.75-3.84%, the cadmium content is 0.60-1.22%, and the Pb content is 0.83-6.43%; the zinc content in the filtrate II is 37.38-55.50 g / L, the Cu content is 0.08-0.32 g / L, and the Cd content is 48.33-127.46 g / L.

6. The method for preparing refined cadmium by deep replacement of double-size zinc powder by ultrasonic enhancement according to claim 1, characterized in that: The total zinc content in the zinc powder of step (3) is 98%-99.5%, the metallic zinc content is 95%-98%, and the impurity content is 0.50%-2%; the temperature of the ultrasonic enhanced replacement reaction is 45-55°C, the time is 30-75 min, and the pH end point is 4-4.8; in terms of mass percentage, the cadmium content in the sponge cadmium is 96.81%-97.11%, the zinc content is 2.88%-2.96%, and the Cu content is 0.082%-0.17%; the cadmium content in the filtrate III is 0.48-1.28 g / L, the zinc content is 83.78-111.26 g / L, and the copper content is 0.04-0.16 g / L.

7. The method for preparing refined cadmium by deep replacement of double-size zinc powder by ultrasonic enhancement according to claim 1, characterized in that: In step (4), the alkali is sodium hydroxide, calcium hydroxide or potassium hydroxide, the smelting temperature is 420-550° C., the smelting time is 1.5-4 h, and the amount of alkali added is 10%-35% of the mass of the sponge cadmium; the cadmium content in the refined cadmium ingot is 99.1-99.9wt.%, and the zinc content is 0.0008-0.004wt.%.

8. The method for preparing refined cadmium by deep replacement of double-size zinc powder by ultrasonic enhancement according to claim 1, characterized in that: The replacement temperature in step (5) is 55-65° C., the pH end point is 4.8-5.5, and the time is 75-120 min. The cadmium content in the filtrate IV is 0.02-0.64 g / L, and the zinc content is 83.78-112.39 g / L. In terms of mass percentage, the Cd content in the zinc-cadmium slag is 18.90%-21.14%, and the zinc content is 75.18%-76.37%.

Citation Information

Patent Citations

  • Method for producing feed-grade zinc sulphate monohydrate and cadmium from zinc cadmium waste residues

    CN107815548A

  • Recovery facility and recovery method of cadmium

    JP2019060007A